Soft computing technique for power control of Triga Mark-II reactor - BABA, AHMET FEVZİ; TOPUZ, VEDAT (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this study, a trajectory tracking fuzzy genetic controller for Istanbul Technical University Triga Mark-II nuclear research reactor design approach is given. Power output of reactor is controlled along the predefined trajectory by fuzzy logic controller. Designed zero order Sugeno type fuzzy logic controller membership boundary value and rule weights are found by genetic algorithm. Non-chattering control with smooth control surface is also achieved using constrained fitness functions. Simulation results shows that reactor power successfully tracks the given trajectory under various working conditions and reaches the desired power level within the determined period within small tracking error. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Fuzzy logic controller; Genetic algorithm; Soft computing; Triga reactor; Trajectory tracking